Increasing Cooking Skills Through Audio-Visual Media in Students of Diponegoro 2 Jakarta - Muhammad Rasyid; Faisal Madani (Jurnal Syntax Admiration, 2023)
Skills can improve students' ability to technical life skill. The learning process that does not vary causes students to be disinterested and bored with handy craft leasons. This study aims to improve the results of learning cooking skills for class VIII students of SMP Diponegoro 2 Jakarta. This research was conducted using the Classroom Action Research method. The subjects of this study were 31 class VIII students. The type of data in this research is qualitative and quantitative in the form of cooking data. Meanwhile, quantitative data is in implementing learning obtained through observation sheets. Based on the research and discussion results, the application of the audio-visual learning model can improve the skills of writing news texts for class VIII students of SMP Diponegoro 2 Jakarta. The results of the cycle I action test can be seen in the presentation. Namely, of the 31 students taking the test, 58% or as many as 18, scored ≥70. While the results of the action test in cycle II with a percentage of 90% or as many as 28 students scored ≥ 70, so was stopped in cycle II because the indicator of research success had been achieved, namely 85%.